Cell commitment motif composed of progenitor‐specific transcription factors and mutual‐inhibition regulation. Issue 4 (1st August 2014) - Wang, Tongpeng; Li, Shanshan; Liu, Yanwei; Wang, Ruiqi
Abstract : Simple mutual‐inhibition networks are frequently occurring motifs in transcriptional regulatory networks for cell lineage commitment. Stable attractors represent cell commitment states. However, how progenitor‐specific transcription factors stabilise progenitor cells and commit them to different cell fates remains unexplained. In this study, the authors represent the cell commitment motifs composed of mutual‐inhibition regulation and progenitor‐specific transcription factors, and develop associated mathematical model to understand how specific cell fate decisions are made. Bifurcation analysis and numerical simulation show that the model could exhibit multiple stable steady states corresponding to progenitor and committed cell states. The transitions between different cell states correspond to different commitment processes. Furthermore, the authors demonstrate that different commitment patterns, for example, haematopoietic and neural fate decisions fall within the scope of proposed framework.